PENGARUH UKURAN PERUSAHAAN, DEBT TO EQUITY RATIO, DAN PROFITABILITAS TERHADAP TAX AVOIDANCE PADA PERUSAHAAN - Yusril Sauqi Niam (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Tax avoidance is an attempt to reduce a company's tax burden while not violating applicable regulations. This study aims to determine the effect of company size, debt to equity and profitability on tax avoidance in household and cosmetic companies. Methods of data analysis carried out by quantitative methods using probability sampling technique. The analysis used is descriptive statistical analysis with the help of the SPSS program. The results of the study show that first, firm size has no effect on tax avoidance, the second variable, debt equity ratio, has no effect on tax avoidance and profitability has an effect on tax avoidance.